The Communication Strategy of the Indonesian Solidarity Party (PSI) in the 2019 General Election Political Campaign in New Zealand - Roennfeld, Sylvia; Permatasari, Yunita; Kyrychenko, Volodymyr (Jurnal Hubungan Internasional, 2021)
This research analyzed the PSI political campaign strategy in gaining votes from overseas voters by taking the case of PSI’s victory in the 2019 general election in New Zealand. The main question in this paper is how the PSI political campaign strategy in New Zealand could win votes in the 2019 general election? To tackle this question, we used a communication strategy theory that emphasizes the vision and mission criteria, programs and activities, objectives and results, audience selection, message formulation, identification of message carriers, and communication/media mechanisms. This research utilized a qualitative method with two data collection techniques—primary and secondary. This research aims to examine the political campaign strategy of PSI in the 2019 general election in gaining overseas voters, specifically focusing on the winning of PSI in New Zealand. This study also aims to draw the campaign strategy, message processing and communication media used to attract overseas voters to gain victory.